C for Dummies 2nd Edition - Gookin, Dan (Wiley Publishing, 2011)
f you’re like most people, the above seems like nonsense. Actually, it’s computer sense—C programming. After digesting C For Dummies, 2nd Edition, you’ll understand it. C programs are fast, concise and versatile. They let you boss your computer around for a change. So turn on your computer, get a free compiler and editor (the book tells you where), pull up a chair, and get going. You won’t have to go far (page 13) to find your first program example. You’ll do short, totally manageable, hands-on exercises to help you make sense of: